Gênero, turismo e comércio de rua: um estudo etnográfico sobre as peixeiras da Ilha do Sal, Cabo Verde - Silva, Maria Iully Melo (2024)
This dissertation focuses on rabidantes of Cape Verde, especifically the female fish sellers of Sal Island. We seek to understand the commercial and sociability relations as well as the networks involved in the constitution of the field of foodstuff selling, taking the intersection of street commerce, gender and tourism as the analytical axis. We characterized the fish sellers' trade on Sal Island, paying attention to the the different cities of Espargos, Pedra Lume, Murdeira, Palmeira and Santa Maria, the latter being the most touristic city in Cape Verde, with a high cost of living and designed directly for tourism, encompassing various enterprises and a considerable tourist structure. Based on this, we prioritized bibliographical research and the production of data from ethnographic research with the female fish sellers of Pontão of Santa Maria, where we highlighted their daily work and protagonism. We understand that rabidancia, as an institution that arose from the development of various alternatives for survival in this island territory predates the tourism model implemented on the island. It also functions as a point of intersection, currently responsible for a vast commercial network that brings together other sectors, as well as the livelihood of several women and their families in Cape Verde.